2016
DOI: 10.1002/j.0022-0337.2016.80.3.tb06086.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Perceived Value of Peer‐Mentoring Clinical Leadership Experiences

Abstract: This pilot study compared second-and fourth-year dental students' perceived values of newly implemented clinical leadership experiences (CLEs) at one U.S. dental school during the 2012-13 academic year. In the CLEs, fourth-year (D4) students mentored second-year (D2) dental students during faculty-supervised patient treatment. The two cohorts' perceived value of the experiences was measured with questionnaires consisting of five-point Likert scale questions and open text responses. Out of a total of 114 D2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Working together and teamwork may not come easily but are fundamental to dentistry 9 . Our results supported previous studies’ findings about the usefulness of PAL as a method to teach teamwork in patient care 4 , 9 , 19 . Despite the fact that students at our institution are not allowed to select their partner, previous research has reported that most peers got along well and performed in a professional and supportive manner 9 , 19 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Working together and teamwork may not come easily but are fundamental to dentistry 9 . Our results supported previous studies’ findings about the usefulness of PAL as a method to teach teamwork in patient care 4 , 9 , 19 . Despite the fact that students at our institution are not allowed to select their partner, previous research has reported that most peers got along well and performed in a professional and supportive manner 9 , 19 .…”
Section: Discussionsupporting
confidence: 89%
“…PAL has been affirmed in studies conducted around the world as creating a teaching environment in which health professions students have learned leadership and teamwork skills 2 , 7 , 9 , 13 , 14 , 18 . Though the benefits of PAL have thus been documented in research, we found only a few published articles about PAL programs in U.S. dental schools 4 , 9 , 19 . Our study sought to extend previously published research by exploring the perspectives of practicing dentists on the applicability of experiencing PAL during dental school.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There is clearly a lack of institutional justice and standards or guidelines with regard to dealing with the issue. No intervention studies in the dentistry field have investigated the role of awareness and education in improving the detection and reporting of abuse [29]. A new strategy should be designed to mitigate violence and abuse against dentists and their staff that involves a combination of individual, organisational, social, and political support.…”
Section: Discussionmentioning
confidence: 99%
“…Informally, this network serves as a resource for incoming and early stage students for questions regarding the daily routine of dental school and advice. Peer to peer mentoring has shown success in professional school settings . Some benefits include increased comfort and guidance, helping the student deal with stressful situations, particularly during the first year of dental school, and later from pre‐clinic to clinic by sharing their experiences with their peers …”
Section: Introductionmentioning
confidence: 99%